A Fragmented Approach to Indonesia's Decentralized Urban Slum Reduction Policy: Central Java's Case - Saru Arifin (Unisia, 2021)
The Indonesian government, through the Ministry of Public Works and Public Housing ('PUPR'), launched a significant campaign in 2015-2019 to eradicate slums from Indonesian cities, termed "Kota Tanpa Kumuh" ('Kotaku') or City Without Slums. While this endeavor has succeeded in physically reducing the number of slums in Indonesia, the objective of totally eliminating slums within that time frame is unattainable. Many Indonesian municipalities continue to have slum communities with a variety of socioeconomic effects. The article argues, through the use of a case study in Central Java Province, that the government's failure to achieve its objective of zero slums in Indonesian cities is due to the Kotaku program's approach being incompatible with that of other ministries. Due to the fact that the problem of slum settlements encompasses a range of societal concerns such as poverty, low income, culture, and even criminality, merely altering the housing in which people live from uninhabitable to respectable is insufficient. Meanwhile, the root causes of slums continue to be ignored. As a result, this article proposes that slum eradication be integrated and sustainable through the continual involvement of numerous essential parties, including NGOs and universities.